p16 Immunohistochemical Expression as a Surrogate Assessment of CDKN2A Alteration in Gliomas Leading to Prognostic Significances - Geyer, Lucas; Wolf, Thibaut; Chenard, Marie-Pierre; Cebula, Helene; Schott, Roland; Noel, Georges; Guerin, Eric; Pencreach, Erwan; Reita, Damien; Entz-Werlé, Natacha; Lhermitte, Benoît (Cancers, 2023)
CDKN2A is a tumor suppressor gene encoding the p16 protein, a key regulator of the cell cycle. CDKN2A homozygous deletion is a central prognostic factor for numerous tumors and can be detected by several techniques. This study aims to evaluate the extent to which immunohistochemical levels of p16 expression may provide information about CDKN2A deletion. A retrospective study was conducted in 173 gliomas of all types, using p16 IHC and CDKN2A fluorescent in situ hybridization. Survival analyses were performed to assess the prognostic impact of p16 expression and CDKN2A deletion on patient outcomes. Three patterns of p16 expression were observed: absence of expression, focal expression, and overexpression. Absence of p16 expression was correlated with worse outcomes. p16 overexpression was associated with better prognoses in MAPK-induced tumors, but with worse survival in IDH-wt glioblastomas. CDKN2A homozygous deletion predicted worse outcomes in the overall patient population, particularly in IDH-mutant 1p/19q oligodendrogliomas (grade 3). Finally, we observed a significant correlation between p16 immunohistochemical loss of expression and CDKN2A homozygosity. IHC has strong sensitivity and high negative predictive value, suggesting that p16 IHC might be a pertinent test to detect cases most likely harboring CDKN2A homozygous deletion.